Feasibility of Optical Atomic Clocks implementing on Global Navigation Satellite System (GNSS) in the Near Future - Wang, Zheyang (Transactions on Computer Science and Intelligent Systems Research, 2024)
This paper evaluates the feasibility and advantages of implementing optical atomic clocks in Global Navigation Satellite System (GNSS). Traditional GNSS relies on atomic clocks that works on microwave frequencies, which, while reliable, have limitations in precision and stability. Optical atomic clocks, operating at higher frequencies and narrower linewidths, promise significantly enhanced precision and stability due to their utilization of highly stable lasers, atomic references, and optical cavities. These improvements could address current shortcomings in GNSS accuracy and reliability. The operation principles of optical atomic clocks are explored, detailing the mechanisms that afford them superior timekeeping capabilities. Additionally, the paper discusses the challenges of integrating these clocks into GNSS, including the need for environmental resilience and compactness, and outlines technological advancements that might overcome these obstacles. The findings suggest that optical atomic clocks could substantially enhance the performance of GNSS, paving the way for more precise global navigation and timing solutions.